2004
DOI: 10.1002/art.20623
|View full text |Cite
|
Sign up to set email alerts
|

Association between nuclear antigens and endogenous retrovirus in the generation of autoantibody responses in murine lupus

Abstract: Objective. (NZB ؋ NZW)F 1 (NZB/NZW) mice and other strains of mice with experimental lupus frequently produce autoantibodies to both chromatin constituents and murine leukemia virus envelope gp70. These autoantibody responses are involved in the glomerulonephritis that develops in these mice. This study was undertaken to explore possible connections between these 2 antigen systems.Methods. We used monoclonal antibodies (mAb) derived from unmanipulated NZB/NZW mice to investigate the specificity of anti-gp70 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
(61 reference statements)
0
11
0
2
Order By: Relevance
“…nuclear Ags can trigger autoimmune responses to chromatin and gp70 (55). We detected no clinical evidence of autoimmune disease during a Ͼ8-mo observation period in which our mice were (repeatedly) vaccinated and challenged with large tumor inocula and developed high specific CD8 T cell immunity.…”
Section: Discussionmentioning
confidence: 64%
“…nuclear Ags can trigger autoimmune responses to chromatin and gp70 (55). We detected no clinical evidence of autoimmune disease during a Ͼ8-mo observation period in which our mice were (repeatedly) vaccinated and challenged with large tumor inocula and developed high specific CD8 T cell immunity.…”
Section: Discussionmentioning
confidence: 64%
“…However, an endogenous retrovirus is not a likely source of dsRNA in B6.NZBc13 mice, as almost all endogenous retroviruses are not replication competent due to post-integration mutations and deletions, suggesting a lack of active viral infection. Moreover, the Sgp3 locus was found to control the gp70 expression of a modified polytropic (mPT) provirus (ssRNA virus), and not of the xenotropic proviruses (NZB-X1 or NZB-X2) shown to accelerate anti-chromatin antibody production in NZB mice [28][29][30]. Interestingly, it has been previously reported that in vivo exposure to poly(I:C) potently increases serum gp70 levels in NZB mice, which suggested a potential role for gp70 as an acute phase reactant [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that, in addition to anti-gp70 Abs, Abs to nuclear material can also bind to NZB xenotropic retroviruses (14), due to the presence of this material on the surface of the retrovirus. The correlation between gp70IC and ANA levels, consistent with both phenotypes being reliant on high levels of gp70, provides support for this theory.…”
Section: Discussionmentioning
confidence: 99%
“…In crosses with the NZB and New Zealand White (NZW) parental strains of the autoimmune (NZB ϫ NZW)F 1 strain, gp70IC levels were linked to the MHC on chromosome 17 (8,12) and to a locus on chromosome 7 (13). Crosses with these strains have also shown linkage of gp70 levels to chromosome 4 (14,15). Furthermore, in crosses with the NZB strain, both gp70 and gp70IC levels were linked to chromosome 13 (8,16).…”
mentioning
confidence: 99%